O processo de constituição identitária dos moradores do Quilombo Carrapatos de Tabatinga (Bom Despacho-MG) - Anna Caroline Oliveira Teixeira Vertelo (2022)
This research seeks to understand the challenges and tensions experienced by the Quilombo Community of Carrapatos de Tabatinga in Bom Despacho - MG, in the identification, recognition and entitlement of the community as a remnant of a quilombo. We intend to describe and analyze the processes of construction of ―quilombola‖/maroon identity in the Community of Tabatinga, from the discourses and narratives of the residents themselves about recognition; relating to the different meanings of the term ―quilombola‖ in the processes of identification and self-identification, understanding this process as a series of events that are motivating and creating new forms of construction and reconstruction of local ethnic identity. The research aims to apprehend the term "quilombola" as a consequence of a complex, heterogeneous process of resemantization, linked to local particularities, in opposition to the meaning of the term as it is manifested in normative texts. It finds it´s place in a moment of identity rescue and resource to blackness as an instrument of legitimization of the struggle agenda and reconfiguration of intra and extra group power relations, which, involved with the problem of the construction of cultural difference, produce new categorizations about the ―culture‖ and social identity of the group.